Model Influence Discovery Learning Regarding Students' Cognitive Learning Outcomes on Changes in Forms of Objects at Islamic Global School Malang Elementary School - Sumita, Maulidia Wiyan; Wedi, Agus; Husna, Arafah (Proceedings Series of Educational Studies, 2024)
Model discovery learning considered quite effective in improving student learning outcomes. The aim of this research is to find out whether there is a model influence discovery learning on students' cognitive learning outcomes on material changing the shape of objects at the Islamic Global School Malang Elementary School. The subjects of this research were class III at SD Islamic Global School Malang. Data collection techniques include interviews with class III teachers, observations, and post-test learning outcomes. this research is using experimental method quasi experiment with research design posttest only control group. In processing data on student learning outcomes using the Independent Sample T-Test with assistance SPSS 25. From the results of data processing, it was found that the Asymp.Sig (2-tailed) value was 0.020 < 0.05, which means the working hypothesis (H1) accepted. It can be concluded that there is a significant influence model discovery learning on students' cognitive learning outcomes on material changing the shape of objects. Keywords: Discovery Learning Model; Cognitive Learning Outcomes